التأثير الأليلوباثي لمستخلصات الباذنجان البري Solanum elaeagnifolium Cav. في إنبات بادرات القمح، ونموها - البـرني ندى; الـمعمار أنـور; إبراهيـم غسـان (Latakia University Journal -Biological Sciences Series, 2019)
يُعدُّ الباذنجان البري Solanum elaeagnifolium Cav. من النباتات الغازية الخطيرة التي تهدِّد زراعة المحاصيل في سورية. دُرس مختبرياً تأثير المستخلصات المائية، ومستخلصات الآيزوبروبانول للأجزاء النباتية من هذا النوع خلال طور النضج التام، في إنبات بادرات صنفين من القمح الطري والقاسي، ونموها. وبيَّنت النتائج أن لمستخلصات الباذنجان البري تأثيراً سلبياً معنوياً في الصفات المدروسة؛ إذ انخفض إنبات حبوب صنفي القمح المدروسين، وازداد الزمن الوسطي للإنبات. كما انخفض متوسط طول السويقة والجذير لبادرات القمح مع ظهور أعراض سمِّية واضحة. ازداد هذا التأثير السلبي مع زيادة التركيز، واختلف بحسب الجزء النباتي، ونوع المستخلص، والتركيز المستخدم، وصنف القمح المختبر. لقد استجاب صنفا القمح المدروسان استجابتين مختلفتين لتأثير مستخلصات النوع S. elaeagnifolium مع ظهور حساسية أكبر لدى القمح القاسي. وبالنتيجة إن مستخلصات نبات الباذنجان البري تحتوي على مركبات كيميائية تسبب التأثير الأليلوباثي في النباتات، وتساهم في قدرتها على غزو الحقول الزراعية، ومنافسة المحصول. Silverleaf Nightshade (Solanum elaeagnifolum Cav.) is a serious invasive weed which threats crops in Syria. In laboratory, the effect of Aqueous extracts and Isopropanol extracts of plant parts of S. elaeagnifolum at maturity stage were tested on germination and seedling growth of two wheat varieties (sativum and durum). Results showed that Silverleaf Nightshade extracts play a negative significant role on studied properties. It is presented by reducing germination of grains of the two wheat varieties and increased the average germination time, and also by decreasing radicle and coleoptile length of wheat seedling with the apperance of clearly phytotoxicity. This effect increases with increasing concentration and differs according to plant part, type of extract, wheat varieties and tested concentration. Results indicated that the two tested wheat varieties responded somehow differently to the allelopathic effect of S. elaeagnifolum extracts, with a greater sensivity shown by durum wheat. In conclusion, extracts of Silverleaf Nightshade contain allelochemicals that may contribute to its invasiveness and extreme competitiveness.